ANTIBIOTIC RESISTANCE TO ESCHERICHIA COLI ISOLATED FROM LAYING HENS - Besung, I Nengah Kerta; Suarjana, I Gusti Ketut; Gelgel, I Ketut Tono Pasek (Buletin Veteriner Udayana, 2019)
The study aim was to determine the resistance of Escherichia coli to antibiotics that isolated in laying hens. A total of 100 samples of chicken feces were taken from Tabanan, Bangli and Karangasem districts. E. coli were isolated and identified by Carter (1990) method, followed by a bacterial susceptibility test with agar diffusion method from Kirby Bauer against antibiotics namely oxytetracycline (30 µg), ampicillin (10 µg), streptomycin (10 µg), sulfamethoxazole (30 µg), chloramphenicol (30 µg), and kanamycin (30 µg). The obtained data compared to the next sensitivity standard of the bacteria that classified as sensitive, intermediate, and resistant. The results showed that E. coli from chicken feces are sensitive to kanamycin, whereas the other antibiotics are intermediate or resistant. The increase in resistance is in line to the age of the chicken.